A construção da cidade: a vida nas ruas, religião, voluntariado e Estado - Priori, Josimar (2018)
This thesis analyzes the construction of the city from a study on the relationships between people living on the streets and their religious, volunteers and state interlocutors. Urban construction is thought from a situational perspective. The city is treated as the result of daily practices and seen from different positions: people living on the streets, religious, volunteers, state agents. The ethnographic research was conducted in the city of Maringá-PR between January 2015 and January 2016, during which I followed the daily life of people living on the streets and the forms of intervention carried out by Christian churches, volunteer groups and state agents. The starting point was the mapping of what life on the streets creates in political and social terms. I observed that life on the streets prompts a series of social practices, which draw attention to their disproportion in relation to the number of people living on the streets and the disagreement (RANCIÈRE, 2006) related to the ways of representing it when it is taken as reference the ways in which street life itself is understood. Thus, at least three cités or ordinances (BOLTANSKI and THEVENOT, 2006) are produced by social actors, at the same time as they provide references to justify their actions. These are religious, voluntary and state ordinances, which create administrative ways, including public policies, to intervene on street life and presuppositions for interpretations of urban order. Religious see life on the streets from the standpoint of sin and spiritual causes, voluntary as scarcity and the state as urban dirt or lack of rights. The former set out to evangelize the people who live on the streets; the latter, in the name of solidarity, to help them, and third parties, on the one hand, to remove them from the field of vision and, on the other hand, to realize their rights. The people who intervene on them become, through this intervention, public agents, militants, good Christians, organizers of the city, in other words, they produce themselves as actors, subjects able to intervene in the issues of interest that are considered as of the city. In short, they constitute themselves as political subjects. People that live on the street, on the other hand, are displaced into a position of recipients of these policies, even though they are by contrast constitutive of them. These subjects, however, elaborate a narrative about themselves that questions the external representations, in addition to creating a set of practices, knowledge and ways of interpreting their life and the contemporary world that oppose this state of things. On the one hand, they make instrumental use and re-signify the resources that the interveners bring to them. On the other, they refuse the terms of orderings assistencial, religious and state ordinances in terms of their assumptions. From this use and contestation, important misunderstandings appear that make us understand more than just ways of managing life on the streets. They also talk about urban conflict and make it possible to observe the main ordering forms of the contemporary social world, which builds the city. Specifically, I argue that life on the streets offers terms for the establishment of the following political subjects: 1) Pentecostal churches, linked to a political-religious project of a nation; 2) individuals who identify themselves as good practitioners, children of God, supporters and builders of new projects of life, as well as professional politicians, militants who think the extension of rights, or are adept at social hygiene; 3) good men who elaborate a solidarity and welcoming city representation; 4) people living on the streets are seen as objects of intervention and priority state management. The overlap between religious, voluntary and state practices about street life seems to me, therefore, a relevant sign to know the ways of building order, power and the contemporary city. Being this mechanism of urban production from the street so recurrent and relevant, nationally and internationally, I suggest in this thesis that it is, sociologically, treated as a structuring mechanism of urban life.